(untitled) (Medico Legal Update, 2020)
Objective: Vitamin D is a an important vitamin which is effect on several system of human body, in this study we determination serum levels of vitamin D in women patients with carpal tunnel syndrome (CTS) and investigation the relation between vitamin D and diabetes on CTS patients. Materials and Method: Subjects of this study enrolled 53 women (33 patients and 20 control), their aged range between (30-50) year. The patients were selected from attendee of out- patient Neurology clinic of Al- Imam Sadiq teaching Hospital, Hilla city, Iraq, in the period from December 2018 to April 2019. Blood samples were taken from subject to determination vitamin D levels. Results: The present study shows a significant (p<0.05) decrease in the mean of vitamin D level in women patients with CTS comparison with control women (15.6±10.2) , (32.7±16.7) respectively. No significant difference was found between vitamin D and diabetes regarding the CTS. Conclusion: The role of vitamin D is the one potential cause of CTS, this study revealed low serum vitamin D level in patient with CTS compared to control .